IMPACT OF PAST RETURN, TURNOVER, VOLATILITY, BID-ASK SPREAD ON DISPOSITION EFFECT (EVIDENCE ON SMALL CAPITAL STOCK LISTED IN INDONESIAN STOCK EXCHANGE IN 2016-2020) - Ariq Khizam Shalahuddin; Erman Denny Arfianto (Diponegoro Journal of Management, 2022)
Stock return is something that moves very randomly and is influenced by many things, so it is complicated to predict. However, on the other hand, investors make stock return assessments to predict the future as the basis for asset valuation. This shows the contradiction caused by the stock return itself. Significant rise and fall of the stock prices, illustrates inefficient market conditions. Behavioral biases occur when investors make investment decisions that are inconsistent or not optimal even though they have been able to process correctly all the information available in the market so that they have the correct probability level about future rates of return. The inclination of individuals to act will then trigger a bias to develop a disposition effect, riding losers too long and winners too short, given the current research gap. As a result of this contradiction, this study aims to look at what factors affect investors behavior in a disposition effect. This research consists of empirical studies done on small - cap stocks listed on the IDX between 2016 and 2020. This study''s research design is a causal design, which recognizes the relationship between other variables or the influence of one variable on other variables. Logit regression will be the research type used in this study. Logit regression is used to analyze separately the sell versus hold decision and the sell versus buy.This research method is quantitative, with a focus on quantity and the usage of secondary data for research. Past Return has a positive and significant effect on Disposition Effect in small stocks. Turnover variable has a positive and significant effect on Disposition Effect in small stocks, because the increased gains and loss coefficients for high turnover stocks are generally double the size of the winner and losser coefficients for stocks with low relative turnover. Volatility has no effect on the disposition effect variable. This is caused by the volatility in small caps are not showing the high of volatility level, the data showed that the volatility in small caps tend to be stable. The bid-ask spread variable has no effect on the Disposition Effect variable because the bid-ask spread in small caps showed that the bid ask spread are all in negative value and no data showed the high difference in between.